The Eportfolio as Support for the Professional Development of Preservice Teachers: a Theoretical and Practical Overview - Karsenti, Thierry; Dumouchel, Gabriel; Collin, Simon (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The portfolio is rapidly gaining attention in initial teacher training programs. It serves multiple uses and ends in the professional development and reflective practice of preservice teachers, and the technical advances of Web 2.0 will only increase the potential for learning opportunities. From now on, portfolio content that was formerly private territory can be generously shared. Against this background, this article provides an overview of the portfolio’s role in initial teacher training programs. The four main functions of the portfolio are addressed, followed by the advantages of the eportfolio over the paper portfolio. A working conceptual framework is then proposed for eportfolio use to support professional development in the Web 2.0 age. To provide a practical application for initial teacher training, we conclude with a presentation of Eduportfolio, an eportfolio that effectively taps the potential of Web 2.0.